Analisis Pemahaman Konsep Pembelajaran Tematik Integratif Menggunakan Sistem Pembelajaran Daring Berbasis E-Learning Moodle pada Mahasiswa Pendidikan Guru Sekolah Dasar Universitas Bengkulu - Nani Yuliantini; Panut Setiono; Yuli Amaliyah (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to describe the understanding of the concept of Integrative Thematic Learning by students of the Bengkulu University Primary School Teacher Education Program through learning in networks based on E-learning Moodle. This research was conducted with a qualitative descriptive method. The subjects in this study were 6th-semester students who attended the Thematic Integrative Learning lectures on Globalization Themes, totaling 40 students. The instruments in this study used interview guidelines and documented the results of the final semester exams. The results showed that students' understanding of concepts in integrated thematic learning lectures learning with moodle e-learning media can be said to be high. This can be seen from the results of the assessment of all students who took lectures as many as 34 people got high scores with a percentage of 85% and as many as 6 people in the medium category by 15%.